Finding the missing heritability of complex diseases. - Manolio, T; Collins, F; Cox, N; Goldstein, D; Hindorff, L; Hunter, D; McCarthy, M; Ramos, E; Cardon, L; Chakravarti, A; Cho, J; Guttmacher, A; et al. (2009)
Genome-wide association studies have identified hundreds of genetic variants associated with complex human diseases and traits, and have provided valuable insights into their genetic architecture. Most variants identified so far confer relatively small increments in risk, and explain only a small proportion of familial clustering, leading many to question how the remaining, 'missing' heritability can be explained. Here we examine potential sources of missing heritability and propose research strategies, including and extending beyond current genome-wide association approaches, to illuminate the genetics of complex diseases and enhance its potential to enable effective disease prevention or treatment.